Age and sequence of emergence of permanent teeth in a population of Costa Rican schoolchildren = Edad y secuencia de erupción de la dentición permanente en una población de niños escolares en Costa Rica - Gutiérrez Marín, Natalia 1975-
The aim of this study was to determine the average age and sequence of eruption of permanent dentition in the school population of the province of Cartago, Costa Rica. Methods: A cross-sectional observational study included children between the ages of 5 and 12 from public and private schools. Clinical examination was performed, and the presence or absence of permanent teeth recorded. Statistical analysis: An estimation of means of eruption was used through binary variables, building the probabilities of the presence of a dental piece through a logistic regression. Results: 833 children were examined: 433 (51.90%) girls and 400 (48.10%) boys. The permanent teeth erupt first in the female sex; however, this difference is not statistically significant. The maxilla eruption sequence for girls was 6-1-2-4-3-5-7 on both sides; for boys, the sequence of eruption was 6-1-2-4-5-3-7 for the right side and 6-1-2-4-3-5-7 for the left side. In the jaw, the sequence in boys was 6-1-2-3-4-5-7, and in girls, 1-6-2-3-4-5-7. Conclusions: For the first time, at the Central American Level, the pattern of permanent dentition eruption could be established. The age of permanent dental eruption does not vary according to sex in this population.